Study on Arsenic Poisoning by Worldwide Drinking Water, its Effects and Prevention: Study on Arsenic Poisoning by Worldwide Drinking Water, its Effects and Prevention - Ullah, Habib; Hussain, Shabbir; Ahmad, Asrar (International Journal of Economic and Environmental Geology, 2019)
The present studies were conducted to evaluate the arsenic poisoning worldwide in drinking water. Arsenic not only contaminates the surface and groundwater but also enters into food chains like vegetables and food staff. Human beings are directly exposed to arsenic poisoning due to consumption of water resources containing arsenic. Sea foods and fish are two main sources of arsenic in human diet. Consumption of arsenic poisoned water can cause severe health problems like cancer, hyperkeratosis, gangrene and peripheral vascular diseases. The arsenic is excreted from the body trough skin, hair, urine, breath etc. Arsenic poisoning can be diagnosed by the measurement of total amount of arsenic in urine. Symptoms of arsenic poisoning include red or swollen skin, changes in the skin color, abdominal pain, vomiting and nausea, diarrhea, cramping of muscles, finger and toe tingling etc. Arsenic poisoning may be relieved through steroid ingestion at its early stage or use of selenium. It is very difficult to remove all the arsenic from water bodies so the main remedy is to stop drinking water having arsenic content. Arsenic poisoning also affects the plant ‘s yield, its reproductive capacity, fertility and fruit production. Arsenic accumulation in plants will damage the cellular membranes and may lead to the leaking of electrolyte.